Compressive, tensile and bending basic creep behaviours related to the same concrete. (3rd June 2013) - Tailhan, Jean‐Louis; Boulay, Claude; Rossi, Pierre; Le Maou, Fabrice; Martin, Eric
Abstract This paper concerns the relationship between compressive, tensile and flexural creep behaviours related to the same concrete. Experimental tests and a numerical simulation are performed in the scope of this work. The main conclusion of this study is that due to the strong scale effect related to the tensile and bending creep behaviours of a "standard" concrete mix design, it is not possible to simulate numerically (with classical Kelvin‐Voigt chains) the bending creep behaviour of that type of concrete knowing the compressive and tensile creep behaviours obtained using the specimen geometries normally used in laboratories.